دراسة بعض مؤشرات جودة مياه الشرب في بعض مصادر مياه الشرب في الساحل السوري - عليا تميم أحمد; سلمان فؤاد علي (Latakia University Journal -Biological Sciences Series, 2014)
تكتسب مصادر المياه في المنطقة الساحلية في سورية أهمية كبيرة نظراً لتنوع مصادر هذه المياه والحاجة الكبيرة إليها كمصادر لمياه الشرب والري، وانطلاقا من ذلك تبذل جهوداً كبيرةً للحفاظ على سلامة هذه المصادر ومنع الملوثات من الوصول إليها. هَدَفَ هذا البحث إلى دراسة تركيز بعض الملوثات الكيميائية في بعض مصادر مياه الشرب المنتشرة في المنطقة الساحلية . وشملت الدراسة قياس تراكيز كل من النترات والنتريت وبعض المعادن الثقيلة مثل الرصاص والكادميوم والتوتياء في عينات مياه أُخذت من خمسة مصادر مياه تمتد من شمال اللاذقية إلى شمال محافظة طرطوس. أظهرت النتائج أن المصادر المائية جميعها تحتوي النترات والنتريت والمعادن الثقيلة المدروسة بتراكيز تختلف حسب المصدر المائي ولكن جميع هذه التراكيز كانت منخفضة وتقع ضمن الحدود المقبولة وفقاً للمواصفة القياسية السورية لمياه الشرب. خلصت الدراسة إلى أن المصادر المائية في المنطقة الساحلية تتميز بنقاوتها نسبياً وانخفاض نسبة الملوثات التي تصل إليها. Water sources in Syrian coastal area have a great importance due to the variety of the sources and the urgent needs to water for drinking and irrigation. Therefore great efforts are made to protect water sources from contaminants. This research aimed to study some contaminant indicators in some drinking water sources in the Syrian coastal area. The study included determining the concentrations of nitrates, nitrites and some heavy metals including lead, cadmium and zinc in water samples taken from five sources of water distributed from north Lattakia to north Tartous. The results showed that the concentrations of nitrate, nitrite and heavy metals differ depending on the water source. However, all these concentrations were lower and within the acceptable limits of Syrian standard for drinking water. The study concluded that water resources in the coastal area are distinguished with their relative purity and contaminants little reach.